تأثير النشاط البدني المكيف على تحسين الحالة الصحية لذوي السمنة المصابين بانقطاع النفس النومـي - عقيب اسمهان/حداد لينة (Institut d’Éducation Physique et Sportive / UNIVERSITY OF MOSTAGANEM, 2025)
جاءت هذه الدراسة بعنوان "تأثير النشاط البدني المكيف على تحسين الحالة الصحية لذوي السمنة المصابين بانقطاع النفس النومـي"، وتهدف إلى تسليط الضوء على فعالية البرامج الحركية الموجهة والمكيفة في تحسين الحالة الصحية للأشخاص الذين يعانون من السمنة المفرطة المصحوبة بانقطاع النفس أثناء النوم، وهي من المشكلات الصحية الشائعة التي تؤثر سلبًا على جودة الحياة. تتجلى أهمية هذا البحث في توضيح العلاقة بين النشاط البدني المكيف ومدى تأثيره على مؤشرات صحية متعددة، مثل تحسين جودة النوم، وتخفيف أعراض انقطاع النفس، وتحسين عناصر اللياقة البدنية المرتبطة بالصحة كالقوة العضلية والقدرة القلبية التنفسية. وقد افترضت الدراسة وجود تأثير إيجابي ملحوظ للنشاط البدني المكيف على الحالة الصحية العامة لهؤلاء الأفراد، إلى جانب وجود فروق واضحة قبل وبعد تطبيق البرنامج من حيث تراجع شدة الأعراض، وتحسن مؤشر كتلة الجسم ومقاييس اللياقة. ولتحقيق أهداف الدراسة، تم اعتماد المنهج التجريبي من خلال تطبيق برنامج بدني مكيف مدته ثلاثة أشهر بواقع ثلاث أيام، شمل مجموعة من التمارين الهوائية وتمارين تقوية العضلات، مع متابعة طبية مستمرة. وتكوّنت العينة من ست نساء تتراوح أعمارهن بين 50 و57 سنة، تم اختيارهن وفق معايير بدقة وتشخيص لانقطاع النفس الليلي المرتبط بالسمنة. // // // // // Résumé: This study, entitled "The effect of physical activity adapted to improve the health condition of obese people with sleep apnea", aims to highlight the effectiveness of motor and air -conditioned motor programs in improving the health condition of people with obesity accompanied by sleep apnea, which is a common health problems that negatively affect the quality of life. The importance of this research is evident in clarifying the relationship between adapted physical activity and its impact on multiple health indicators, such as improving sleep quality, relieving symptoms of self -cutting, and improving physical fitness elements associated with health such as muscle strength and respiratory heart ability. The study assumed the existence of a noticeable positive effect of physical activity adapted to the general health of these individuals, in addition to the presence of clear differences before and after the application of the program in terms of declining symptoms, and improving the body mass index and fitness standards. To achieve the objectives of the study, the experimental curriculum was adopted by applying a three -month air - addition to the presence of clear differences before and after the application of the program in terms of declining symptoms, and improving the body mass index and fitness standards. To achieve the objectives of the study, the experimental curriculum was adopted by applying a three -month air -conditioned physical program, which included a group of air exercises and muscle strengthening exercises, with continuous medical follow -up. The sample consisted of six women between the ages of 50 and 57 years, who were chosen according to strict and diagnosis of obesity -associated with obesity. In this context, a group of means and devices were used to collect data and measurements related to the health status of the participants, such as the electronic scale of weight measurement, the length tape, the grip meter (dynamometer), the flexibility measuring box, and the ocean measurement tape, in addition to the elastic device to measure the skin folds, to ensure a comprehensive evaluation of fitness and physical health elements with scientific accuracy. The results showed that adapted physical activity effectively contributed to reducing seizures, improving sleep quality, lowering weight, and preventing chronic diseases such as cardiovascular disease and type 2 diabetes, highlighting the importance of adopting these programs within the rehabilitation and health protection centers. In conclusion, the study recommends the generalization of motor programs directed within the non -pharmaceutical treatment protocols conditioned physical program, which included a group of air exercises and muscle strengthening exercises, with continuous medical follow -up. The sample consisted of six women between the ages of 50 and 57 years, who were chosen according to strict and diagnosis of obesity -associated with obesity. In this context, a group of means and devices were used to collect data and measurements related to the health status of the participants, such as the electronic scale of weight measurement, the length tape, the grip meter (dynamometer), the flexibility measuring box, and the ocean measurement tape, in addition to the elastic device to measure the skin folds, to ensure a comprehensive evaluation of fitness and physical health elements with scientific accuracy. The results showed that adapted physical activity effectively contributed to reducing seizures, improving sleep quality, lowering weight, and preventing chronic diseases such as cardiovascular disease and type 2 diabetes, highlighting the importance of adopting these programs within the rehabilitation and health protection centers. In conclusion, the study recommends the generalization of motor programs directed within the non -pharmaceutical treatment protocols for obesity patients and sleep problems, for obesity patients and sleep problems, while emphasizing the involvement of multidisciplinary teams to ensure comprehensive and effective sponsorship in this category.
LAPA-2025-4
Keywords: النشاط البدني المكيف; الحالة الصحية; السمنة; انقطاع النفس النومـي